ANTESEDEN DAN KONSEKUENSI BRAND EXPERIENCE SEKOLAH SWASTA: STUDI EMPIRIS PERILAKU SISWA SMA XYZ DI MEDIA SOSIAL [ANTECEDENTS AND CONSEQUENCES OF PRIVATE SCHOOL BRAND EXPERIENCE: AN EMPIRICAL STUDY OF XYZ HIGH SCHOOL STUDENTS' BEHAVIOR ON SOCIAL MEDIA] - Suwu, Selvi Esther; Antonio, Ferdi (Universitas Pelita Harapan, 2024)
Technology, especially the internet, is becoming the main platform and source of learning, so students understand more about the internet and social media and this can be an experience they feel so that it is likely to be expressed on social media. Schools can see opportunities to be able to attract consumer attention with the existence of experience stories about their schools (Brand Experience) on social media through the behavior of students who write them. The purpose of this study is to examine the influence of private school Brand Experience antecedents and their consequences on the behavior of XYZ High School students on social media. The research methodology is quantitative with 196 XYZ school respondents in South Tangerang, the data obtained is processed with SMART PLS ver 3. The results obtained are evidence of the influence of antecedents, namely positive Brand Identification on Brand Experience, resulting in consequences of student behavior that tells good things and promotions about XYZ schools (Advocacy Intention and EWOM) on social media. Bahasa Indonesia Abstrak Pandemi covid 19 membuat pembelajaran di sekolah yang biasa secara tatap muka menjadi online, sehingga untuk melakukannya memerlukan pengetahuan tentang teknologi dan mengakibatkan adanya penyesuaian bagi siswa juga sekolah. Teknologi terutama internet menjadi platform dan sumber utama pembelajaran, jadi siswa tambah mengerti tentang internet dan media sosial dan hal ini bisa jadi pengalaman yang mereka rasakan sehingga kemungkinan dituangkan di media sosial. Sekolah dapat melihat peluang untuk dapat menarik perhatian konsumen dengan adanya cerita pengalaman mengenai sekolahnya (Brand Experience) di media sosial melalui perilaku siswa yang menuliskannya. Tujuan penelitian ini adalah ingin mengkaji pengaruh anteseden Brand Experience sekolah swasta dan konsekuensinya pada perilaku siswa SMA XYZ di media sosial. Metodologi penelitian ialah kuantitatif dengan 196 responden sekolah XYZ di Tangerang Selatan, data yang diperoleh diolah dengan SMART PLS ver 3. Hasil yang didapatkan adalah adanya bukti pengaruh anteseden yaitu Brand Identification yang positif terhadap Brand Experience sehingga menghasilkan konsekuensi perilaku siswa yang menceritakan hal baik dan promosi tentang sekolah XYZ (Advocacy Intention dan EWOM) di media sosial.